LOCAL GENIUS MASYARAKAT JAWA KUNO DALAM RELIEF CANDI PRAMBANAN - Mufti Riyani Riyani (Program Studi Pendidikan Sejarah - Universitas Samudra, 2015)
Following F.D.K. Bosch (1952), Local genius is cultural member ability to proving as much as strength their cultural character basic face to cultural acculturation. The meaning of local genius by experts is the local approach to society intellectual of the cultural member. Ancient Javanese as artifact producers of Borobudur and Prambanan monumental cultural that symbolized by Hinduism and Buddhism, more, ancient Javanese of Islamic Mataram was learned Hinduism value to being Javanese cultural (Damami, 2002: 85). According to the reason, ancient Javanese original cultural still be surviving. Ancient Javanese local ability has risen in the cultural as the complexity of activity and cultural product. Relief is one of the complexities of cultural product that could be exhibiting local genius. Relief is the ornament that carved at the body of a temple. The ornaments motif at the body of Prambanan as one of the biggest temples in Java has imagined local ability of Javanese in accepting Hinduism cultural. The local ability exhibited by the creativity of curving artist in their independency and capability to the meaning of Javanese original characterized. The Characteristic and originality could be imagined ancient Javanese ability.